Soft magnetic powder, dust core, magnetic element, and electronic device
By optimizing the particle size and composition of soft magnetic powder, the problems of high eddy current loss and low magnetic characteristics caused by large particle size of soft magnetic powder in the prior art are solved, and a powdered magnetic core with low iron loss and high magnetic characteristics are realized, which is suitable for magnetic components in electronic equipment.
Patent Information
- Application Number
- CN202411395665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-11
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing soft magnetic powders have high eddy current losses and low magnetic characteristics of the powdered magnetic core due to large particle sizes.
A soft magnetic powder with an average particle size of 2.0 μm or more and 10.0 μm or less and an average roundness of particles is 0.80 or more and 0.95 or less, and its composition includes Fe, Si, Cr, Sn and impurities. By optimizing the content of these elements and the particle shape, fillability and magnetic properties are improved.
A soft magnetic powder with small particle size and excellent filling properties is realized, and a powdered magnetic core with low iron loss and good magnetic characteristics is produced, which is suitable for magnetic components in electronic equipment.
Smart Images

Figure CN119811818A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to soft magnetic powder, pressed powder magnetic core, magnetic element and electronic equipment. Background Art
[0002] Patent Document 1 discloses a soft magnetic powder having a composition represented by Fe-2% Si-1% Cr-1% Sn and an average particle size of 55 μm or 200 μm. In addition, in the soft magnetic powder, the crystal particle size is optimized. As a result, a powder core having low core loss when excited at a predetermined excitation frequency can be realized.
[0003] Patent Document 1: Japanese Patent Application Publication No. 2008-124270
[0004] The soft magnetic powder described in Patent Document 1 has a technical problem that the eddy current loss is high when it is made into a powder magnetic core due to its large particle size. In addition, there is a technical problem that the magnetic properties of the powder magnetic core are degraded due to its low filling property when the powder is pressed.
[0005] Therefore, the technical problem of the present invention is to realize a soft magnetic powder having a small particle size and excellent filling properties, and capable of producing a powder magnetic core with low iron loss and excellent magnetic properties. Summary of the invention
[0006] The soft magnetic powder involved in the application example of the present invention is composed of Fe as a main component, Si with a content of not less than 2.5 mass% and not more than 7.5 mass%, Cr with a content of not less than 1.0 mass% and not more than 10.0 mass%, Sn with a content of not less than 0.05 mass% and not more than 1.10 mass% and impurities, and has an average particle size of not less than 2.0 μm and not more than 10.0 μm, and an average roundness of the particles of not less than 0.80 and not more than 0.95.
[0007] A powder magnetic core according to an application example of the present invention includes the soft magnetic powder according to an application example of the present invention.
[0008] A magnetic element according to an application example of the present invention includes the powder magnetic core according to the application example of the present invention.
[0009] An electronic device according to an application example of the present invention includes the magnetic element according to the application example of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a plan view schematically showing a toroidal coil component.
[0011] Figure 2 It is a perspective view schematically showing a closed magnetic circuit type coil component.
[0012] Figure 3It is a perspective view showing a mobile personal computer as an electronic device including the magnetic element according to the embodiment.
[0013] Figure 4 It is a plan view showing a smartphone as an electronic device including the magnetic element according to the embodiment.
[0014] Figure 5 It is a perspective view showing a digital camera as an electronic device including the magnetic element according to the embodiment.
[0015] Description of Reference Numerals
[0016] 10: coil component; 11: pressed powder core; 12: wire; 20: coil component; 21: pressed powder core; 22: wire; 100: display unit; 1000: magnetic element; 1100: personal computer; 1102: keyboard; 1104: main body; 1106: display unit; 1200: smart phone; 1202: operation button; 1204: receiver; 1206: microphone; 1300: digital camera; 1302: housing; 1304: light receiving unit; 1306: shutter button; 1308: memory. DETAILED DESCRIPTION
[0017] Hereinafter, the soft magnetic powder, the powder magnetic core, the magnetic element, and the electronic device of the present invention will be described in detail based on the preferred embodiments shown in the drawings.
[0018] 1. Soft magnetic powder
[0019] The soft magnetic powder according to the embodiment is a metal powder exhibiting soft magnetism and can be used for any purpose, for example, by binding particles together via a binder to produce various powder bodies such as powder cores and wave absorbing materials.
[0020] 1.1. Composition
[0021] The soft magnetic powder contains Fe (iron) as a main component, Si (silicon) having a content of 2.5 mass % to 7.5 mass %, Cr (chromium) having a content of 1.0 mass % to 10.0 mass %, Sn (tin) having a content of 0.05 mass % to 1.10 mass %, and impurities.
[0022] The main component refers to an element having the highest content rate based on the atomic ratio. Fe is the main component of the soft magnetic powder and has a great influence on the basic magnetic properties of the soft magnetic powder.
[0023] The content of Fe is not particularly limited, but is preferably 80 mass % or more, more preferably 90 mass % or more.
[0024] The content of Si is 2.5% by mass or more and 7.5% by mass or less, preferably 2.7% by mass or more and 5.0% by mass or less, and more preferably 3.0% by mass or more and 4.5% by mass or less. If the content of Si is within the range, a powder compact with higher magnetic permeability can be obtained. It should be noted that if the content of Si is lower than the lower limit, magnetic properties such as magnetic permeability and DC superposition characteristics are reduced. On the other hand, if the content of Si is higher than the upper limit, the soft magnetic powder becomes hard, so the density of the powder compact is reduced.
[0025] The Cr content is greater than 1.0% by mass and less than 10.0% by mass, preferably greater than 3.0% by mass and less than 6.0% by mass, and more preferably greater than 4.0% by mass and less than 5.0% by mass. If the Cr content is within the above range, the oxidation resistance of the soft magnetic powder can be improved. As a result, a soft magnetic powder in which the proportion of oxides is suppressed to a particularly low level during powder pressing and a powder press having good magnetic properties such as magnetic permeability and DC superposition characteristics can be produced. It should be noted that if the Cr content is lower than the above lower limit, the oxidation resistance of the soft magnetic powder is reduced. On the other hand, if the Cr content is higher than the above upper limit, magnetic properties such as magnetic permeability and DC superposition characteristics are reduced.
[0026] The content of Sn is 0.05% by mass or more and 1.10% by mass or less, preferably 0.07% by mass or more and 0.80% by mass or less, and more preferably 0.10% by mass or more and 0.40% by mass or less. If the content of Sn is within the range, the particle shape of the soft magnetic powder can be made closer to a sphere. Thus, a small particle size can also improve the filling property of the soft magnetic powder and can improve the density of the powder compact. It should be noted that if the content of Sn is lower than the lower limit, the roundness of the particle shape becomes lower and the filling property decreases. Therefore, the density of the powder compact decreases, and the magnetic properties such as magnetic permeability and DC superposition characteristics decrease. On the other hand, if the content of Sn is higher than the upper limit, the soft magnetic powder is easily oxidized and the oxygen content increases. The oxides produced by oxidation will reduce the proportion of metal in the powder compact, thereby causing the density of the powder compact to decrease, and the magnetic properties such as magnetic permeability and DC superposition characteristics to decrease.
[0027] In addition, the mass ratio of the content of Sn to the content of Cr is set to Sn / Cr. The mass ratio Sn / Cr is preferably greater than 0.02 and less than 0.30, more preferably greater than 0.03 and less than 0.25, and further preferably greater than 0.04 and less than 0.20. If the mass ratio Sn / Cr is within the range, the balance between the content of Cr and the content of Sn can be optimized. Thus, it is possible to take into account both the improvement of the filling property based on the particle shape and the improvement of the magnetic properties based on the optimization of the composition. As a result, a powder compact having particularly good magnetic properties can be obtained.
[0028] It should be noted that if the mass ratio Sn / Cr is lower than the lower limit, the oxidation resistance of the soft magnetic powder is improved, but the roundness of the particle shape may become lower, and the filling property of the soft magnetic powder is reduced. On the other hand, if the mass ratio Sn / Cr is higher than the upper limit, the sphericalization of the soft magnetic powder can be achieved, but the oxidation resistance may be reduced, and the proportion of metal in the powder compact is reduced.
[0029] The soft magnetic powder may contain other elements as impurities in addition to the elements described above. Impurities refer to elements that are inevitably mixed in except for the elements described above.
[0030] Regarding the concentration of impurities, each element is preferably 0.10 mass % or less, more preferably 0.05 mass % or less. In addition, the total concentration of impurities is preferably 1.00 mass % or less. It should be noted that if within this range, even if other elements are included, it will not affect the effect exerted by the soft magnetic powder, so it is allowed to contain.
[0031] In addition, the soft magnetic powder involved in the embodiment may also contain oxygen as an impurity. Oxygen is sometimes mixed in the raw materials or the manufacturing process. Based on the mass ratio, the oxygen content of the soft magnetic powder is preferably less than 3000ppm, more preferably less than 2000ppm, and further preferably less than 1500ppm. As a result, the degradation of the particle shape caused by the surface adhesion of the oxide can be suppressed, so a soft magnetic powder with high filling property during powder pressing can be obtained. In addition, the reduction in the proportion of metal in the powder compact can be suppressed. On the other hand, the lower limit value may not be set, but from the viewpoint of ensuring the insulation between particles, the lower limit value of the oxygen content is preferably more than 300ppm, more preferably more than 500ppm. As a result, the insulation between particles can be fully ensured, and a powder compact with suppressed eddy current loss can be obtained.
[0032] The above composition was determined by analytical means as described below.
[0033] Examples of the analytical means include the iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, the iron and steel-ICP emission spectrometry specified in JIS G 1258:2007, the iron and steel-spark discharge emission spectrometry specified in JIS G 1253:2002, the iron and steel-fluorescent X-ray analysis specified in JIS G 1256:1997, and the gravimetric-titration-absorptiometry specified in JIS G1211 to G 1237.
[0034] Specific examples include a solid-state emission spectrometer manufactured by SPECTRO, particularly a spark discharge emission spectrometer, model number: SPECTROLAB, type: LAVMB08A, and an ICP device CIROS120 manufactured by Rigaku Corporation.
[0035] In addition, in particular, the determination of C (carbon) and S (sulfur) was carried out by using the oxygen flow combustion (high frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211: 2011. Specifically, the carbon-sulfur analyzer CS-200 manufactured by LECO Corporation is used.
[0036] Furthermore, in particular, in determining N (nitrogen) and O (oxygen), the iron and steel-nitrogen quantitative method specified in JIS G 1228: 1997 and the oxygen quantitative method general rules for metal materials specified in JIS Z 2613: 2006 were used. Specifically, the oxygen-nitrogen analyzer TC-300 / EF-300 manufactured by LECO and the oxygen-nitrogen-hydrogen analyzer ONH836 manufactured by LECO are listed.
[0037] 1.2.Powder characteristics
[0038] The average particle size of the soft magnetic powder is 2.0 μm to 10.0 μm, preferably 3.0 μm to 10.0 μm, and more preferably 4.0 μm to 9.0 μm. This can provide a soft magnetic powder having high packing properties during compacting and capable of suppressing eddy current loss in the compact.
[0039] It should be noted that if the average particle size of the soft magnetic powder is lower than the lower limit, the soft magnetic powder becomes easy to aggregate, so that the filling property is reduced and the density of the powder compact is reduced. On the other hand, if the average particle size of the soft magnetic powder is higher than the upper limit, the eddy current loss of the powder compact may increase.
[0040] The average particle size refers to a particle diameter D50 at which the cumulative frequency from the smaller diameter side is 50% in the volume-based cumulative particle size distribution of the soft magnetic powder obtained using a laser diffraction particle size distribution analyzer.
[0041] The average roundness of the soft magnetic powder is greater than 0.80 and less than 0.95, preferably greater than 0.82 and less than 0.92, and more preferably greater than 0.85 and less than 0.90. Thus, a soft magnetic powder having particularly good filling properties when pressed can be obtained. In addition, when an insulating film is formed on the surface of the particles of the soft magnetic powder, the film can be formed uniformly and without spots. Thus, a powder compact having excellent insulation between particles can be manufactured. In addition, by forming the film uniformly and without spots, the specific surface area can be reduced, and therefore the amount of adhesive covering the surface can also be reduced. Therefore, the amount of adhesive bonding between particles is reduced, thereby improving the magnetic properties of the powder compact.
[0042] It should be noted that if the average roundness is lower than the lower limit, the filling property of the soft magnetic powder during powder pressing is reduced. In addition, the uniformity of the film thickness of the insulating coating is reduced. On the other hand, if the average roundness is higher than the upper limit, the difficulty of manufacturing the soft magnetic powder becomes higher.
[0043] The average circularity of the soft magnetic powder is measured in the manner described below.
[0044] First, an image (secondary electron image) of the soft magnetic powder is taken by a scanning electron microscope (SEM). Next, the obtained image is read into image processing software. Regarding image processing software, for example, image analysis type particle size distribution measurement software "Mac-View" manufactured by Mountech Co., Ltd. is used. It should be noted that the shooting magnification is adjusted so that more than 50 and less than 100 particles are captured in one image. Then, multiple images are obtained to obtain a total of more than 300 particle images.
[0045] Next, the roundness of more than 300 particle images is calculated using software, and the average value is obtained. The average value obtained is used as the average roundness of the soft magnetic powder. It should be noted that when the roundness is set to e, the area of the particle image is set to S, and the perimeter of the particle image is set to L, the roundness e is obtained by the following formula.
[0046] e=4πS / L 2
[0047] The particles of the soft magnetic powder may contain a plurality of crystal grains. That is, the particles of the soft magnetic powder may contain a polycrystalline structure. The number of crystal grains per unit area of the cross section of the particle is preferably 0.10 [pieces / (μm) 2 ] or more and 0.45 [pieces / (μm) 2 ] or less, more preferably 0.14 [pieces / (μm) 2 ] or more and 0.38 [pieces / (μm) 2 ] or less, more preferably 0.16 [pieces / (μm) 2 ] or more and 0.35 [pieces / (μm)2 ] or less. If the number of crystal grains per unit area of the cross section of the particles is within the above range, the number density of the crystal grains can be optimized, and as a result, the crystal grain size can be optimized. As a result, a soft magnetic powder can be obtained in which the particles are appropriately deformed during powder compaction and a high-density powder compact can be produced. In addition, the magnetic permeability depending on the crystal grain size is sufficiently improved, and a soft magnetic powder with low eddy current loss can be obtained.
[0048] The number of crystal grains per unit area of the cross section of the particles of the soft magnetic powder is measured in the following manner.
[0049] First, the cross section of the soft magnetic powder particles is etched with a 3% nitric acid alcohol (Nital) etching solution (3% nitric acid, 97% ethanol). Next, the cross section of the particles is photographed with a scanning transmission electron microscope (STEM). Next, the obtained image is read into image processing software. For example, the image analysis type particle size distribution measurement software "Mac-View" manufactured by Mountech Co., Ltd. can be used as the image processing software.
[0050] Next, the cross-sectional area (cross-sectional area) of the particle is calculated. The cross-sectional area is calculated by calculating the major and minor diameters of the cross section, and then using the calculation formula (cross-sectional area = major diameter × minor diameter × π ÷ 4).
[0051] In addition, the image processing software is used to detect the crystal grains contained in the cross-sectional image. Next, the number of crystal grains contained in the cross-sectional area of a particle is counted. Then, the number of crystal grains counted is divided by the cross-sectional area to calculate the number of crystal grains per unit area of the cross-sectional area (the number density of crystal grains). The unit is set to pieces / (μm) 2 .
[0052] 1.3. Insulation coating
[0053] If necessary, an insulating film may be provided on the surface of the soft magnetic powder particles. By providing such an insulating film, the insulation between the soft magnetic powder particles can be improved. As a result, the eddy current flowing between the particles can be suppressed, and the eddy current loss in the powder compact can be suppressed.
[0054] Examples of the insulating coating include glass materials, ceramic materials, and resin materials.
[0055] 1.4. Tap density and compacted powder density
[0056] The tap density of the soft magnetic powder is preferably 3.80 g / cm 3 Above and 5.10g / cm 3 Below, more preferably 3.90g / cm 3 Above and 5.00g / cm 3Below, more preferably 4.00 g / cm 3 Above and 5.00g / cm 3 Below. If the tap density is within the above range, a soft magnetic powder having particularly good filling properties can be obtained. Thus, a higher density powder compact can be manufactured. It should be noted that if the tap density is lower than the above lower limit, the filling properties of the soft magnetic powder may be reduced, and the density of the powder compact may be reduced. On the other hand, if the tap density is higher than the above upper limit, the difficulty of manufacturing the soft magnetic powder may increase.
[0057] The tap density of the soft magnetic powder is measured in the manner described below.
[0058] First, the soft magnetic powder was treated with a coupling agent. Phenyltrimethoxysilane was used as the coupling agent. Next, the tap density of the treated soft magnetic powder was measured using a powder property evaluation device. A powder tester (Powder Tester) PT-X manufactured by Hosokawa Micro Co., Ltd. was used as the powder property evaluation device.
[0059] In addition, the density of the powder compact obtained by compacting the soft magnetic powder at a pressure of 294 MPa is preferably 5.30 g / cm 3 Above and 6.10g / cm 3 Below, more preferably 5.50g / cm 3 Above and 6.00g / cm 3 As a result, a soft magnetic powder having particularly good filling properties and low manufacturing difficulty can be obtained. As a result, a higher density powder compact can be produced.
[0060] 1.5. Specific surface area
[0061] The specific surface area of the soft magnetic powder is preferably 0.170 m 2 / g or more and 0.320m 2 / g or less, more preferably 0.180m 2 / g or more and 0.300m 2 / g or less, more preferably 0.190m 2 / g or more and 0.280m 2 / g or less. If the specific surface area is within the above range, the filling property of the soft magnetic powder can be improved, and the density of the powder compact can be improved. It should be noted that if the specific surface area is lower than the above lower limit, the particle size of the soft magnetic powder may be too large, and the iron loss of the powder compact may increase. On the other hand, if the specific surface area is higher than the above upper limit, the filling property of the soft magnetic powder may be reduced, and the density of the powder compact may be reduced.
[0062] The specific surface area of the soft magnetic powder is obtained by the BET method. As an example of a specific surface area measuring device, there is a BET specific surface area measuring device HM1201-010 manufactured by Mountech Co., Ltd. The amount of the test object is 5 g.
[0063] 1.6. Magnetic permeability
[0064] The magnetic permeability of the soft magnetic powder according to the embodiment when it is made into a green compact is preferably 30 or more, and more preferably 32 or more at a measurement frequency of 1 MHz. Such a soft magnetic powder can realize a green compact with high magnetic permeability.
[0065] The magnetic permeability of the powder compact is the real part μ' of the complex magnetic permeability, and the BH analyzer is used for its measurement, and the measurement frequency is set to 1 MHz. In addition, the number of turns of the winding wire relative to the powder compact is 7, and the wire diameter of the winding wire is set to 0.5 mm. In addition, when manufacturing the powder compact, 2% by mass of epoxy resin of the soft magnetic powder is used as a binder. Furthermore, the size of the powder compact is set to an outer diameter of φ14 mm, an inner diameter of φ8 mm, and a thickness of 3 mm, and the molding pressure is set to 294 MPa.
[0066] 1.7. DC superposition characteristics
[0067] As described above, the soft magnetic powder involved in the embodiment has excellent filling properties and can produce a high-density powder compact. The high-density powder compact has a high DC superposition characteristic. The DC superposition characteristic generally refers to the permeability characteristic brought about by the applied DC magnetic field when an AC current is superimposed on a DC current in an AC circuit using a magnetic element. In this specification, when the permeability when an AC magnetic field is superimposed on a DC magnetic field is reduced by 30% from the permeability when no DC magnetic field is applied, the size of the DC magnetic field at that time point is treated as the DC superposition characteristic. If the DC superposition characteristic based on this definition is high, the high permeability can be maintained until a high applied magnetic field. It should be noted that the permeability when measuring the DC superposition characteristic in this specification is the real part μ' of the complex permeability measured using a BH analyzer, and the measurement frequency is set to 10kHz.
[0068] The DC superposition characteristic of the soft magnetic powder according to the embodiment when made into a powder compact is preferably 15000 [A / m] or more, more preferably 16000 [A / m] or more. The soft magnetic powder having such DC superposition characteristic is suitable for high current applications with a high magnetic field applied.
[0069] 1.8.Coercive force
[0070] The coercive force of the soft magnetic powder involved in the embodiment is preferably 12.0 [Oe] or less (955 [A / m] or less), more preferably 10.0 [Oe] or less (796 [A / m] or less), and further preferably 8.0 [Oe] or less (637 [A / m] or less). If the coercive force is within the above range, the hysteresis loss in the powder compact can be suppressed. In addition, from the perspective of ease of manufacturing the soft magnetic powder, the coercive force is preferably 2.0 [Oe] or more (159 [A / m] or more), and more preferably 3.0 [Oe] or more (239 [A / m] or more).
[0071] The coercive force of the soft magnetic powder can be measured by a vibrating sample type magnetometer, etc. The maximum applied magnetic field when measuring the coercive force is, for example, 15 kOe.
[0072] 2. Method for producing soft magnetic powder
[0073] Next, an example of a method for producing the above-mentioned soft magnetic powder will be described.
[0074] The soft magnetic powder can be a powder produced by any method. As an example of a production method, in addition to various atomization methods such as water atomization, gas atomization, and cyclone atomization, a pulverization method and the like can also be cited. Among them, for the soft magnetic powder, it is preferred to use a powder produced by an atomization method. According to the atomization method, the particle shape is closer to a true sphere and the formation of oxides and the like is less, and high-quality metal powder can be efficiently produced. Therefore, a metal powder with a smaller specific surface area can be produced by an atomization method.
[0075] The atomization method is a method of producing metal powder by causing a high-speed jet of liquid or gas to impact a molten metal, thereby refining the molten metal and cooling it. In the atomization method, the molten metal is refined and then solidified, and then spherical particles are produced, so particles that are closer to a true sphere can be produced.
[0076] The water atomization method is a method of producing metal powder from molten metal by using a liquid such as water as a coolant, spraying it in an inverted cone shape so that it converges to one point, and causing molten metal to flow toward the convergence point and impact it.
[0077] The cyclone atomization method is a method of producing metal powder by supplying a coolant along the inner circumference of a cooling cylinder to rotate along the inner circumference, and spraying a liquid or gas spray onto the molten metal to take the dispersed molten metal into the coolant.
[0078] The gas atomization method is a method of producing metal powder from molten metal by using gas as a cooling medium, spraying it in an inverted cone shape that converges at one point, and causing molten metal to flow toward the convergence point and impact it.
[0079] In these atomization methods, the number density of crystal grains in the particle cross section of the soft magnetic powder can be adjusted according to the conditions.
[0080] The pouring temperature of the melting temperature is preferably set to Tm+200°C or higher, more preferably Tm+220°C or higher and Tm+350°C or lower, and further preferably Tm+250°C or higher and Tm+300°C or lower relative to the melting point Tm[°C] of the constituent material of the soft magnetic powder. Thus, when the powder is refined by various atomization methods and solidified, it is possible to ensure that the time it exists as molten metal is longer than before. Thus, the number density of the crystal grains in the particle cross section of the soft magnetic powder can be adjusted to within the range described above.
[0081] In the atomization method, the molten metal is made to flow out from a very fine opening, and the obtained thin stream of molten metal is made to impact the fluid spray. The outer diameter of the thin stream of molten metal is not particularly limited, and is preferably less than 2.5 mm, more preferably greater than 0.3 mm and less than 2.0 mm, and further preferably greater than 0.5 mm and less than 1.5 mm. As a result, it is easy to make the molten metal evenly align with the fluid spray, so it is easy to make droplets of appropriate size evenly dispersed. As a result, the average particle size of the soft magnetic powder can be adjusted to within the range described above. In addition, since the cooling rate is faster, the oxygen content of the soft magnetic powder can be adjusted to within the range described above. Moreover, since the amount of molten metal supplied within a certain period of time is suppressed, the cooling rate of each droplet also becomes uniform, and it is easy to adjust the number density of grains in the particle cross section of the soft magnetic powder to within the range described above.
[0082] The produced soft magnetic powder may be classified as necessary. Examples of the classification method include dry classification such as sieving classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.
[0083] 3.Powder cores and magnetic components
[0084] Next, the powder magnetic core and the magnetic element according to the embodiment will be described.
[0085] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, a solenoid valve, a generator, etc. In addition, the powder magnetic core according to the embodiment can be applied to the magnetic core of these magnetic elements.
[0086] Hereinafter, two types of coil components will be described as examples of magnetic elements.
[0087] 3.1. Ring type
[0088] First, a toroidal coil component as an example of the magnetic element according to the embodiment will be described.
[0089] Figure 1 It is a plan view schematically showing a toroidal coil component.
[0090] Figure 1 The coil component 10 shown includes a ring-shaped powder magnetic core 11 and a conductive wire 12 wound around the powder magnetic core 11. Such a coil component 10 is generally called a toroidal coil.
[0091] The powder core 11 is obtained by supplying a mixture obtained by mixing the soft magnetic powder involved in the embodiment with a binder to a molding die and performing pressure molding. Therefore, the powder core 11 is a powder body containing the soft magnetic powder involved in the embodiment. With regard to such a powder core 11, the filling property can be improved even if a small-diameter soft magnetic powder is used, so it will become a powder core with low iron loss and high density. Therefore, when the coil component 10 is mounted on an electronic device, etc., it is possible to achieve high performance and miniaturization of the electronic device, etc.
[0092] As the constituent material of the binder used to make the powder magnetic core 11, for example, organic materials such as silicone resin, epoxy resin, phenol resin, polyamide resin, polyimide resin, polyphenylene sulfide resin, etc., phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, cadmium phosphate, inorganic materials such as silicates such as sodium silicate, etc., and thermosetting polyimide or epoxy resin is particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. Therefore, the manufacturing ease and heat resistance of the powder magnetic core 11 can be improved.
[0093] The ratio of the binder to the soft magnetic powder may vary slightly depending on the magnetic properties, mechanical properties, and allowable eddy current losses of the powder magnetic core 11 to be manufactured, but is preferably 0.3% by mass or more and 5.0% by mass or less, more preferably 0.5% by mass or more and 3.0% by mass or less, and further preferably 0.7% by mass or more and 2.0% by mass or less. Thus, the particles of the soft magnetic powder can be fully bonded to each other, and the coil component 10 having excellent magnetic properties can be obtained.
[0094] If necessary, various additives may be added to the mixture for any purpose.
[0095] The conductive wire 12 may be made of a material having high conductivity, such as a metal material including Cu, Al, Ag, Au, Ni, etc. In addition, an insulating film may be provided on the surface of the conductive wire 12 as necessary.
[0096] The shape of the powder core 11 is not limited to Figure 1 The ring shape shown may be, for example, a shape in which a part of the ring is missing, a shape in which the long side direction is a straight line, a sheet shape, a film shape, or the like.
[0097] The powder core 11 may contain soft magnetic powder or non-magnetic powder other than the soft magnetic powder according to the above-described embodiment, as necessary.
[0098] 3.2. Closed magnetic circuit type
[0099] Next, a closed magnetic path type coil component will be described as an example of the magnetic element according to the embodiment.
[0100] Figure 2 It is a perspective view schematically showing a closed magnetic circuit type coil component.
[0101] Next, a closed magnetic circuit type coil component will be described. In the following description, the differences from the annular type coil component will be mainly described, and descriptions of the same matters will be omitted.
[0102] like Figure 2 As shown, the coil component 20 involved in this embodiment is obtained by burying a coil-shaped conductive wire 22 inside a powder core 21. That is, the coil component 20 as a magnetic element has a powder core 21 containing the soft magnetic powder described above, and the conductive wire 22 is cast from the powder core 21. The powder core 21 has the same structure as the powder core 11 described above. As a result, a powder core 21 with low iron loss and high density can be achieved.
[0103] In addition, the coil component 20 of such a form can be easily reduced in size. Therefore, when the coil component 20 is mounted on an electronic device or the like, the electronic device or the like can achieve higher performance and smaller size.
[0104] Furthermore, since the conductive wire 22 is buried inside the powder core 21, a gap is unlikely to be formed between the conductive wire 22 and the powder core 21. Therefore, the vibration of the powder core 21 caused by the magnetic bias can be suppressed, and the generation of noise associated with the vibration can be suppressed.
[0105] It should be noted that the shape of the powder core 21 is not limited to Figure 2 The shape shown may also be a sheet, a film, etc.
[0106] Furthermore, the powder core 21 may contain soft magnetic powder or non-magnetic powder other than the soft magnetic powder according to the above-described embodiment, as necessary.
[0107] 4. Electronic devices
[0108] Next, based on Figure 3 to Figure 5, an electronic device having a magnetic element involved in an implementation manner is described.
[0109] Figure 3 It is a perspective view showing a mobile personal computer as an electronic device including a magnetic element according to the embodiment. Figure 3 The personal computer 1100 shown in the figure includes a main body 1104 having a keyboard 1102 and a display unit 1106 having a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 includes a magnetic element 1000 such as a choke coil, an inductor, a motor, etc. for a switching power supply.
[0110] Figure 4 It is a plan view showing a smartphone as an electronic device including the magnetic element according to the embodiment. Figure 4 The smartphone 1200 shown in the figure has a plurality of operation buttons 1202, an earpiece 1204, and a microphone 1206. In addition, the display unit 100 is arranged between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 has magnetic components 1000 such as an inductor, a noise filter, and a motor.
[0111] Figure 5 13 is a perspective view showing a digital camera as an electronic device including a magnetic element according to an embodiment. The digital camera 1300 generates an imaging signal by photoelectrically converting light and shadow of a subject through an imaging element such as a CCD (Charge Coupled Device).
[0112] Figure 5 The digital camera 1300 shown in the figure has a display unit 100 provided on the back of a housing 1302. The display unit 100 functions as a viewfinder for displaying an electronic image of a subject. In addition, a light receiving unit 1304 including an optical prism, a CCD, etc. is provided on the front side of the housing 1302, that is, the inner side in the figure.
[0113] When the photographer confirms the subject image displayed on the display unit 100 and presses the shutter button 1306, the CCD imaging signal at that time is transferred and stored in the memory 1308. Such a digital camera 1300 also has a magnetic element 1000 such as an inductor or a noise filter.
[0114] As an electronic device according to an embodiment of the present invention, in addition to Figure 3 Personal computers, Figure 4 Smartphones, Figure 5In addition to digital cameras, examples include: mobile phones, tablet terminals, clocks, inkjet ejection devices such as inkjet printers, portable personal computers, televisions, video cameras, video recorders, car navigation devices, pagers, electronic notebooks, electronic dictionaries, calculators, electronic game equipment, word processors, workstations, video phones, anti-theft TV monitors, electronic binoculars, POS terminals, electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, medical equipment such as electronic endoscopes, fish finders, various measuring equipment, instruments for vehicles, aircraft, and ships, mobile body control equipment such as automobile control equipment, aircraft control equipment, railway vehicle control equipment, and ship control equipment, flight simulators, etc.
[0115] As described above, such an electronic device includes the magnetic element according to the embodiment. Thus, the effect of the magnetic element according to the embodiment including the powder magnetic core having low iron loss and high density can be enjoyed, and the electronic device can be made more functional and smaller.
[0116] 5. Effects of implementation methods
[0117] As described above, the soft magnetic powder according to the embodiment is composed of Fe as a main component, Si with a content of 2.5 mass % or more and 7.5 mass % or less, Cr with a content of 1.0 mass % or more and 10.0 mass % or less, Sn with a content of 0.05 mass % or more and 1.10 mass % or less, and impurities. In addition, the average particle size is 2.0 μm or more and 10.0 μm or less, and the average roundness of the particles is 0.80 or more and 0.95 or less.
[0118] According to such a configuration, a soft magnetic powder having a small particle size and high filling property can be obtained, and a green compact having low iron loss and high density can be produced.
[0119] In the soft magnetic powder according to the embodiment, the oxygen content is 300 ppm or more and 3000 ppm or less.
[0120] According to such a configuration, a soft magnetic powder capable of producing a green compact having a high density and suppressed eddy current loss can be obtained.
[0121] In the soft magnetic powder according to the embodiment, the tap density is 3.80 g / cm 3 Above and 5.10g / cm 3 Below, the specific surface area is 0.170m 2 / g or more and 0.320m 2 / g or less.
[0122] According to such a configuration, a soft magnetic powder having good filling properties despite a small diameter can be obtained, thereby making it possible to produce a green compact having lower iron loss and high density.
[0123] In the soft magnetic powder according to the embodiment, the coercive force is 12.0 [Oe] or less (955 [A / m] or less).
[0124] According to such a configuration, a powder compact having suppressed hysteresis loss can be obtained.
[0125] The density of the powder compact obtained by compacting the soft magnetic powder according to the embodiment at a pressure of 294 MPa is 5.30 g / cm 3 Above and 6.10g / cm 3 the following.
[0126] According to such a configuration, a soft magnetic powder having particularly good filling properties and low manufacturing difficulty can be obtained, thereby making it possible to manufacture a green compact with a higher density.
[0127] In the soft magnetic powder according to the embodiment, when the mass ratio of the content of Sn to the content of Cr is represented by Sn / Cr, Sn / Cr is 0.02 or more and 0.30 or less.
[0128] According to such a configuration, the balance between the Cr content and the Sn content can be optimized. Thus, it is possible to achieve both improved packing properties based on particle shape and improved magnetic properties based on optimized composition. As a result, a powder compact having particularly good magnetic properties can be obtained.
[0129] In the soft magnetic powder according to the embodiment, the particle contains a plurality of crystal grains, and the number of crystal grains per unit area of the cross section of the particle is 0.10 [pieces / (μm) 2 ] or more and 0.45 [pieces / (μm) 2 ]the following.
[0130] According to such a configuration, the number density of the crystal grains contained in the particles can be optimized, and as a result, the crystal grain size can be optimized. As a result, the particles are appropriately deformed during powder compaction, and a soft magnetic powder capable of manufacturing a high-density powder compact can be obtained. In addition, a soft magnetic powder having a sufficiently high magnetic permeability depending on the crystal grain size and low eddy current loss can be obtained.
[0131] The powder magnetic core according to the embodiment includes the soft magnetic powder according to the embodiment. Thus, the filling property of the soft magnetic powder is high, and a powder magnetic core with high magnetic permeability can be obtained. In addition, a powder magnetic core with low iron loss can be obtained.
[0132] Furthermore, the magnetic element according to the embodiment includes the powder magnetic core according to the embodiment. Thus, a magnetic element that can be easily reduced in size and has high performance can be obtained.
[0133] Furthermore, the electronic device according to the embodiment includes the magnetic element according to the embodiment, thereby achieving higher performance and smaller size of the electronic device.
[0134] The soft magnetic powder, powder core, magnetic element and electronic device of the present invention are described above based on preferred embodiments, but the present invention is not limited thereto. For example, the shapes of the powder core and magnetic element are not limited to the shapes shown in the figure, but may be any shapes.
[0135] Example
[0136] Next, specific embodiments of the present invention will be described.
[0137] 6. Manufacture of soft magnetic powder
[0138] 6.1. Sample No.1
[0139] First, a soft magnetic powder was obtained by a water atomization method. The composition of the obtained soft magnetic powder is shown in Table 1. It should be noted that the production conditions of the soft magnetic powder by the water atomization method are shown in Table 1.
[0140] The average particle size, average circularity, oxygen content, and number of crystal grains per unit area of the obtained soft magnetic powder were measured.
[0141] Furthermore, Table 1 shows the difference between the pouring temperature and the melting point and the outer diameter of the thin stream of the molten metal as the production conditions of the soft magnetic powder.
[0142] 6.2. Sample No. 2 to 23
[0143] Except that the composition of the soft magnetic powder was changed as shown in Table 1, Table 2 or Table 3, a soft magnetic powder was obtained in the same manner as Sample No. 1.
[0144] In addition, in Tables 1 to 3, among the soft magnetic powders of each sample No., those corresponding to the present invention are referred to as “Examples”, and those not corresponding to the present invention are referred to as “Comparative Examples”.
[0145] 7. Evaluation of soft magnetic powder
[0146] 7.1. Tap density of soft magnetic powder
[0147] The tap density of the soft magnetic powder of each sample No. is measured. The measurement results are shown in Tables 1 to 3.
[0148] 7.2. Specific surface area of soft magnetic powder
[0149] The specific surface area of the soft magnetic powder of each sample No. is measured. The measurement results are shown in Tables 1 to 3.
[0150] 7.3. Coercive force of soft magnetic powder
[0151] The coercive force of the soft magnetic powder of each sample No. is measured. The measurement results are shown in Tables 1 to 3.
[0152] 7.4. Density of powder compact
[0153] Using the soft magnetic powder of each sample No., a green compact was produced in the following manner.
[0154] First, a mixed material was obtained by mixing soft magnetic powder, epoxy resin (binder) and methyl ethyl ketone. The amount of epoxy resin added was 2% by mass relative to the soft magnetic powder.
[0155] Next, the obtained mixed material was stirred and then dried at 150° C. for 30 minutes to obtain a block-shaped dry product. Next, the dry product was passed through a sieve with a mesh size of 600 μm and pulverized to obtain a granulated powder.
[0156] Next, the obtained granulated powder was filled into a molding die to obtain a compact under the following molding conditions.
[0157] ・Molding method: Pressurized molding
[0158] ・Shape of molded body: Ring
[0159] ・Molding size: outer diameter φ14mm, inner diameter φ8mm, thickness 3mm
[0160] ・Molding pressure: 294MPa
[0161] Next, the binder in the molded body is cured by heating, thereby obtaining a green compact.
[0162] Next, the mass of the obtained green compact was measured, and the density of the green compact was calculated based on the measured mass and the volume of the molded body. The calculation results are shown in Tables 1 to 3.
[0163] 7.5. DC superposition characteristics of powder compacts
[0164] The DC superposition characteristics were measured for the green compacts produced using the soft magnetic powders of the respective sample Nos. The measurement results are shown in Tables 1 to 3.
[0165] 7.6. Iron loss of powder compact
[0166] The iron loss was measured for the green compact produced using the soft magnetic powder of each sample No. The conditions for measuring the iron loss are as follows.
[0167] ・Measurement device: BH analyzer, SY-8258 manufactured by Iwasaki Tsushinki Co., Ltd.
[0168] ・Measurement frequency: 900kHz
[0169] ・Number of windings: 36 turns on the primary side, 36 turns on the secondary side
[0170] ・Wire diameter of winding wire: 0.5mm
[0171] ・Maximum magnetic flux density: 50mT
[0172] Next, the measured iron loss was evaluated with reference to the following evaluation criteria. The evaluation results are shown in Tables 1 to 3. It should be noted that the reference values in the following evaluation criteria are the iron loss measured for the powder compact of Sample No. 7 in the powder compact shown in Table 1 and Table 3, and the iron loss measured for the powder compact of Sample No. 16 in the powder compact shown in Table 2.
[0173] A: Iron loss is less than 100% of the reference value
[0174] B: Iron loss is greater than 100% and less than 110% of the reference value
[0175] C: Iron loss is greater than 110% of the reference value
[0176]
[0177]
[0178]
[0179] As shown in Tables 1 to 3, the soft magnetic powder of each embodiment has a small particle size, a high tap density, and a small specific surface area, and is therefore considered to have high filling properties. In addition, it can be seen that by using the soft magnetic powder of each embodiment, a low iron loss and high density powder compact can be obtained. Moreover, it can be seen that the coercive force of the powder compact is low and the DC superposition characteristics are high. In addition, by optimizing the number of grains per unit area of the particle cross section of the soft magnetic powder, it is possible to achieve low iron loss and high density of the powder compact.
[0180] In contrast, the powder compacts produced using the soft magnetic powders of the comparative examples could not achieve low iron loss or high density. In addition, it was found that the DC superposition characteristics were low.
Claims
1. A soft magnetic powder, characterized in that: The soft magnetic powder is formed of Fe as a main component, Si having a content of 2.5 mass % or more and 7.5 mass % or less, Cr having a content of 1.0 mass % or more and 10.0 mass % or less, Sn having a content of 0.05 mass % or more and 1.10 mass % or less, and impurities, The average particle size is 2.0 μm or more and 10.0 μm or less, The average circularity of the particles is 0.80 or more and 0.95 or less.
2. The soft magnetic powder according to claim 1, characterized in that The oxygen content is 300 ppm or more and 3000 ppm or less.
3. The soft magnetic powder according to claim 1 or 2, characterized in that Tap density is 3.80g / cm 3 Above and 5.10g / cm 3 the following, The specific surface area is 0.170m 2 / g or more and 0.320m 2 / g or less.
4. The soft magnetic powder according to claim 1 or 2, characterized in that The coercive force is less than 12.0 Oe or less than 955 A / m.
5. The soft magnetic powder according to claim 1 or 2, characterized in that: The density of the powder compact obtained by compacting at a pressure of 294 MPa is 5.30 g / cm 3 Above and 6.10g / cm 3 the following.
6. The soft magnetic powder according to claim 1 or 2, characterized in that: When the mass ratio of the content of Sn to the content of Cr is represented by Sn / Cr, the Sn / Cr is 0.02 or more and 0.30 or less.
7. The soft magnetic powder according to claim 1 or 2, characterized in that: The particle comprises a plurality of crystal grains, The number of the crystal grains per unit area of the cross section of the particle is 0.10 grains / μm 2 Above and 0.45 / μm 2 the following.
8. A powder magnetic core, characterized in that: Contains the soft magnetic powder according to claim 1 or 2.
9. A magnetic element, characterized in that: A powder magnetic core according to claim 8 is provided.
10. An electronic device, characterized in that: A magnetic element according to claim 9.
Citation Information
Patent Citations
METHOD OF REDUCING CORE LOSS OF Fe-Si-BASED DUST CORE
JP2008124270A